Emergency transport for obstetric emergencies: integrating community-level demand creation activities for improved access to maternal, newborn, and child health services in northern Nigeria - Oguntunde O; Yusuf FM; Nyenwa J; Dauda DS; Salihu A; Sinai I (Dove Medical Press, 2018)
Olugbenga Oguntunde,1,2 Farouk Musa Yusuf,1,3 Jabulani Nyenwa,1,4 Dauda Sulaiman Dauda,1,2 Abdulsamad Salihu,1,3 Irit Sinai5 1UKAid/Nigeria MNCH2 Programme, Kano, Nigeria; 2Palladium, Abuja, Nigeria; 3Society for Family Health, Abuja, Nigeria; 4Palladium, London, UK; 5Palladium, Washington, DC, USA Purpose: Ensuring adequate access to skilled birth attendants during and after childbirth is a key strategy to reducing maternal and newborn mortalities. Transportation difficulties in emergency situations continue to be a significant barrier to accessing emergency obstetric care, especially in rural and hard-to-reach areas. Emergency transport schemes (ETS) have been introduced in various settings to increase access to emergency care and reduce the second obstetric delay with varying degrees of success. This qualitative study assessed the perceptions of stakeholders and beneficiaries of ETS in two states in northern Nigeria, comparing two models of ETS: one in which the ETS were introduced as a stand-alone intervention, and another in which ETS were part of a package of interventions for increasing demand and improving utilization of maternal and newborn health services.Methods: We carried out focus group discussions with ETS drivers, mothers who delivered in the past year and utilized ETS, husbands of women who benefited from the schemes in the past year, health care providers, traditional birth attendants, and religious leaders, supplemented by in-depth interviews with program focal persons.Results: Demand creation activities – especially working with traditional birth attendants and religious leaders – provided a strong linkage between the ETS and families of women in need of emergency transport services. Community members perceived the ETS model that included demand-generating activities as being more reliable and responsive to women’s needs.Conclusion: ETS remain a key solution to lack of transport as a barrier to utilizing maternal and newborn health services in emergency situations in many rural and hard-to-reach communities. Programs utilizing ETS to improve access to emergency obstetric care should explore the potential of increasing their utility and reach by integrating the schemes with additional demand-side interventions, especially engagement with traditional birth attendants and religious leaders. Keywords: emergency transport, maternal health, emergency obstetric care, access, northern Nigeria